Financial feasibility of a 2500 sow weaned pig operation - Heid, Brent (Kansas State University, 2008)
Lone Tree Farms, Inc. is a diversified agricultural enterprise located in Harrisonville, Missouri. Since operations began in 1962, the hog operation has been expanded to the present size of a 2500 sow farrow-to-wean operation. The results of the thesis research lead Lone Tree Farms believes that there are economic and efficiency reasons behind adding to the existing farrow-to-wean operation with a 2500 sow farrow-to-wean operation. The thesis confirms and reveals several points. First, the project takes between 9 months and a year to complete. Some of the inputs required are eight more personnel and an additional 90,000 bushel of feed grain per operating year. Approximately 3,000 gilts are utilized to stock the project and building costs of approximately $3.5 million dollars will be accrued. The total costs of developing the project will be approximately $4.25 to 4.5 million dollars before the first pig is sold (2007 US Dollars). Many risk factors affect the outcome of the project, including risk of high grain prices due to ethanol, labor needs, environmental issues, and manure utilization needs of the project. The spreadsheet model that was developed as part of this thesis reveals that low productivity of the sow herd is the greatest risk factor for the success of the project. Reducing pigs weaned per sow from 11.0 to 8.5 would lower projected return on equity from 32.7. to 7.6% and increase the cost to produce a weaned pig by $8.72/pig. A major change in both corn (over $2.50/bu) and soybean meal (over $200/ton) price would be required for feed cost to have a similar impact on the cost to produce a weaned pig. The start-up and initial production year pose the greatest challenges and risks. After that, production flows should reach more consistency and effectively lower the risk. The initial start-up capitalization of approximately 30% reduces exposure and liquidity risks. The timing of the project should be made when both input expenses and output prices (pig price) are able to be managed. Combined with good management which maximizes pigs/sow weaned, the project stands a very good chance of being considered successful.
Keywords: Swine; Economics; Business Plan; Weaned Pigs; Breeding; Sow; Agriculture, Animal Culture and Nutrition (0475); Agriculture, General (0473); Economics, Agricultural (0503)